Kegiatan Penyulaman Pohon Mangrove Guna Mengurangi Erosi Pantai di Pulo Cangkir Desa Kronjo Kecamatan Tangerang Provinsi Banten - Dewi, Irma Nurmala; Khaerudin, Dedy; Gandara, Ganjar Sidik; Putra, Arta Rusidarma; Budiharjo, Budiharjo; Putri, Aulia; Noviani, Sika (Journal of Digital Community Services, 2025)
The region of Indonesia, composed mainly of oceans, is not unfamiliar to us as we encounter mangrove plants along the coastlines. Many mangrove ecosystems are damaged and have not been replanted due to a lack of socialization and public awareness of the importance of mangroves for the coastal environment, marine ecosystems, and wildlife around the beach. This community service activity aims to inspire and raise public awareness about the role and function of mangroves. Meanwhile, the method used is a descriptive qualitative method where interviews and field studies are conducted directly, along with the implementation of socialization and a question-and-answer session with the community, the Head of the Mangrove Forest Farmers Group, and the community service team. The mangrove farmers' group enthusiastically received the results of this community service, as did the youth leaders and the community in Kronjo Village. In addition to engaging in direct activities such as replanting mangroves, the community service team also participated in socialization activities to ensure the preservation of mangroves. The community ultimately gained knowledge about the roles and functions of mangroves as a result of this community service activity, and they became more enthusiastic about the preservation of mangrove sustainability for the sake of ecosystem and environmental conservation, as well as effectively addressing coastal erosion in Kronjo Village, which is located on Cangkir Island.